1995
DOI: 10.1038/bjc.1995.397
|View full text |Cite
|
Sign up to set email alerts
|

Alternative promoter usage and mRNA splicing pathways for parathyroid hormone-related protein in normal tissues and tumours

Abstract: (Martin et

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 25 publications
(6 reference statements)
8
71
0
1
Order By: Relevance
“…Human PTHrP expression is regulated predominantly on the transcriptional level by three different promoters (P1-P3). Of these, the P3 promoter (formerly called P2 promoter) has been shown to be active in all breast cancer cells [17]. Within this promoter, three regulatory DNA elements, an Ets, a stimulating protein-1 (Sp1) and a Smad3/4-binding site, have…”
Section: Introductionmentioning
confidence: 99%
“…Human PTHrP expression is regulated predominantly on the transcriptional level by three different promoters (P1-P3). Of these, the P3 promoter (formerly called P2 promoter) has been shown to be active in all breast cancer cells [17]. Within this promoter, three regulatory DNA elements, an Ets, a stimulating protein-1 (Sp1) and a Smad3/4-binding site, have…”
Section: Introductionmentioning
confidence: 99%
“…Southby et al have reported that in their study, the splicing of exon VI to exon VII or exon IX was evident in all samples of RCC, suggesting that the 139-and 141-amino acid isoforms were common; in contrast, the 173-amino acid isoform was less often present. 8 Although the present study confirmed that these newly established cells produce all three isoforms, it has not been determined how these differing C-terminal regions may act biologically and thus which isoforms may play a key role in the development of hypercalcemia in patients. Furthermore, distinct secretory forms of PTHrP arising from these three transcripts have not yet been identified.…”
Section: Discussionmentioning
confidence: 41%
“…In SMRC-1, the number of chromosomes varied from 92 to 100 and the modal number was 95. The representative G-banded karyotype was 95~99 < 4n >, XXYY, +1 [7], +1 [3], add(1)(p36) [8], add(1) [6], der(1;3)(q10;p10) [9], der(1;3) [7], +2 [7], -3 [8], -3 [4], add(3)(q13) [4], del(3)(q27) [7], del (3) [3], +8~21mar. In SMRC-3, the number of chromosomes varied from 42 to 47 and the modal number was 45.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations